A major role for Tau in neuronal DNA and RNA protection in vivo under physiological and hyperthermic conditions - Violet, Marie; Delattre, Lucie; Tardivel, Meryem; Sultan, Audrey; Chauderlier, Alban; Caillierez, Raphaelle; Talahari, Smail; Nesslany, Fabrice; Lefebvre, Bruno; Bonnefoy, Eliette; Buee, Luc; Galas, Marie-Christine (Frontiers in Cellular Neuroscience, 2014)
Nucleic acid protection is a substantial challenge for neurons, which are continuously exposed to oxidative stress in the brain. Neurons require powerful mechanisms to protect DNA and RNA integrity and ensure their functionality and longevity. Beside its well known role in microtubule dynamics, we recently discovered that Tau is also a key nuclear player in the protection of neuronal genomic DNA integrity under reactive oxygen species (ROS)-inducing heat stress (HS) conditions in primary neuronal cultures. In this report, we analyzed the capacity of Tau to protect neuronal DNA integrity in vivo in adult mice under physiological and HS conditions. We designed an in vivo mouse model of hyperthermia/HS to induce a transient increase in ROS production in the brain. Comet and TUNEL assays demonstrated that Tau protected genomic DNA in adult cortical and hippocampal neurons in vivo under physiological conditions in wild-type and Tau-deficient (KO-Tau) mice. HS increased DNA breaks in KO-Tau neurons. Notably, KO-Tau hippocampal neurons in the CA1 subfield restored DNA integrity after HS more weakly than the dentate gyrus neurons. The formation of phosphorylated histone H2AX foci, a double-strand break marker, was observed in KO-Tau neurons only after HS, indicating that Tau deletion did not trigger similar DNA damage under physiological or HS conditions. Moreover, genomic DNA and cytoplasmic and nuclear RNA integrity were altered under HS in hippocampal neurons exhibiting Tau deficiency, which suggests that Tau also modulates RNA metabolism. Our results suggest that Tau alterations lead to a loss of its nucleic acid safeguarding functions and participate in the accumulation of DNA and RNA oxidative damage observed in the Alzheimer’s disease brain.